Hubungan Media Online Kampus Suara Mahasiswa dengan Pemenuhan Kebutuhan Informasi Mahasiswa - Nadyta Hana Radhiyah; Ferry Darmawan (Bandung Conference Series: Journalism, 2023)
Abstract. Information is like daily food that cannot be separated from human needs. Humans access information with various motives and different goals for each individual. Currently, all mediums to access information have been made easier from various platforms. Thus, this study discusses the relationship between Suara Mahasiswa campus online media and meeting student information needs. Researchers want to know the relationship related to several aspects of news value which include extraordinaryness, actuality, and news information in the campus online media of the Suara Mahasiswa with meeting student information needs which are reviewed by four aspects according to McQuail, namely diversion needs, personal relationships, personal identity, and supervision. This study uses a quantitative approach with the correlational method, and uses the SPSS application to help calculate the data distributed through questionnaires. Researchers strengthen the research by looking for objects using random cluster sampling technique. This study uses the Uses and gratification theory as the basis for its work. The results of this study prove that there is a significant relationship between the campus online media coverage of the Suara Mahasiswa and the fulfillment of the needs of students of the Faculty of Communication Sciences class of 2019, which is supported by seven related indicators. Abstrak. Informasi ibarat makanan sehari-hari yang tak lepas dari kebutuhan manusia. Manusia mengakses informasi dengan berbagai motif dan tujuan yang berbeda-beda tiap individunya. Kala ini segala medium untuk mengakses informasi telah dipermudah dari berbagai platform. Dengan begitu penelitian ini membahas tentang hubungan media online kampus Suara Mahasiswa dengan pemenuhan kebutuhan informasi mahasiswa. Peneliti ingin mengetahui hubungan terkait beberapa aspek nilai berita yang diantaranya keluarbiasaan, aktualitas, dan informasi berita dalam media online kampus Suara Mahasiswa dengan pemenuhan kebutuhan informasi mahasiswa yang ditinjau oleh empat aspek menurut McQuail yaitu kebutuhan diversi, hubungan personal, identitas personal, dan pengawasan. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional, serta menggunakan aplikasi SPSS untuk membantu menghitung data yang disebarkan melalui kuesioner. Peneliti memperkuat penelitian dengan mencari objek menggunakan teknik random cluster sampling. Penelitian ini menggunakan teori Uses and gratification sebagai landasan pengerjaannya. Hasil penelitian ini membuktikan bahwa adanya hubungan yang signifikan antara pemberitaan media online kampus Suara Mahasiswa dengan pemenuhan kebutuhan mahasiswa Fakultas Ilmu Komunikasi angkatan 2019 yang didukung oleh tujuh indikator terkait.